2014
DOI: 10.1111/bcp.12169
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based drug design of catechol-O-methyltransferase inhibitors for CNS disorders

Abstract: Catechol-O-methyltransferase (COMT) is of great importance in pharmacology because it catalyzes the metabolism (methylation) of endogenous and xenobiotic catechols. Moreover, inhibition of COMT is the drug target in the management of central nervous system (CNS) disorders such as Parkinson's disease due to its role in regulation of the dopamine level in the brain. The X-ray crystal structures for COMT have been available since 1994. The active sites for cofactor and substrate/inhibitor binding are well resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…It is well-known that COMT is at herapeutic target for the treatment of variousc entral and peripheral nervous system disorders, and increasing interests have been witnessed in the development of COMT inhibitors. [16] Encouraged by the above mentioned findings, 3-BTD was subsequently employeda s af luorescent substratef or rapid screening of COMT inhibitors using both recombinantC OMT and U87-MG S9 as enzyme sources. As shown in Figure 3, the inhibitory tendency and IC 50 value of ak nown COMT inhibitor (tolcapone) were highly consistent in both recombinant COMT (IC 50 = 12.65 nm)a nd U87-MG S9 (IC 50 = 17.12 nm).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that COMT is at herapeutic target for the treatment of variousc entral and peripheral nervous system disorders, and increasing interests have been witnessed in the development of COMT inhibitors. [16] Encouraged by the above mentioned findings, 3-BTD was subsequently employeda s af luorescent substratef or rapid screening of COMT inhibitors using both recombinantC OMT and U87-MG S9 as enzyme sources. As shown in Figure 3, the inhibitory tendency and IC 50 value of ak nown COMT inhibitor (tolcapone) were highly consistent in both recombinant COMT (IC 50 = 12.65 nm)a nd U87-MG S9 (IC 50 = 17.12 nm).…”
Section: Resultsmentioning
confidence: 99%
“…In 2000, the first bisubstrate inhibitor of COMT was reported by the Diederich group. 58,59 Compound 10 (IC 50 = 2 μ M for COMT) was designed via a computational method based on the crystal structure of the COMT complex with Mg 2+ , SAM, and 3,5-dinitrocatechol (Figure 5a). Kinetic analysis showed that this compound is a competitive inhibitor for SAM and a noncompetitive inhibitor for catechol, suggesting that it may go through a “two-step” binding by occupying the SAM binding site first.…”
Section: Development Of Sah Analogs As Mtase Inhibitorsmentioning
confidence: 99%
“…It can be seen that the X-ray structure based design is quite successful in the development of COMT bisubstrate inhibitors. 59 However, for PMT bisubstrate inhibitors, the inhibition profiles in response to structure change seem to be difficult to predict, probably due to dedicated structural difference of binding domains in different MTases subtypes. Therefore, vigorous examination of the crystal structure of the enzyme complex is desired.…”
Section: Development Of Sah Analogs As Mtase Inhibitorsmentioning
confidence: 99%
“…It is well known that COMT is a therapeutic target for the treatment of various central and peripheral nervous system disorders, and increasing interest has been seen in the development of COMT inhibitors. 20,31 At present, the identication and characterization of COMT inhibitors are usually conducted in vitro using recombinant COMT or tissue fractions as enzyme sources. It should be pointed out that the in vivo potency of COMT inhibitors should be assessed in laboratory animals during preclinical studies.…”
Section: Discussionmentioning
confidence: 99%